Computing systems in a pseudomarine operational environment: design and initial test results - Ayodele A. Periola; Sunday O. Adegbola; Rafiu I. Salawu (The Proceedings of the Nigerian Academy of Science, 2021)
Contemporary research recognizes the need to reduce the cooling costs of data centre systems. This is beneficial and also reduces the operational costs. The operational costs can be reduced by using water for cooling instead of relying on conventional cooling systems comprising airconditioners, chillers and cooling towers. The cooling effect of water can be leveraged by siting the underwater data centre in a marine or pseudomarine environment. A pseudomarine environment is considered here since it overcomes the operational challenges associated with obtaining the regulatory permits required to access the marine environment. In addition, the discussion in the paper presents the design of a desktop computing system that uses water for cooling in a pseudomarine environment. The performance test of the desktop computing system is conducted in Oyo, Oyo State Nigeria. This is done to examine the viability of designing and using minidata centres sited in a pseudomarine environment in Nigeria. The initial results indicate that a personal desktop computer in the role of the mini data centre is able to support the execution of software installation without the use of conventional cooling i.e fans for a period exceeding 25 minutes. In this case, the cooling is realized using the emulated pseudo marine environment.